The European revolutions, 1848-1851 - Sperber, Jonathan, 1952- (Cambridge University Press, 2005)
Reaching from the Atlantic to Ukraine, from the Baltic to the Mediterranean, the revolutions of 1848 brought millions of people across the European continent into political life. Nationalist aspirations, social issues and feminist demands coming to the fore in the mid-century revolutions would reverberate in continental Europe until 1914 and beyond. Yet the new regimes established then proved ephemeral, succumbing to counter-revolution. In this second edition, Jonathan Sperber has updated and expanded his study of the European Revolutions between 1848-1851. Emphasizing the socioeconomic background to the revolutions, and the diversity of political opinions and experiences of participants, the book offers an inclusive narrative of the revolutionary events and a structural analysis of the reasons for the revolutions' ultimate failure. A wide-reaching conclusion and a detailed bibliography make the book ideal both for classroom use and for a general reader wishing a better knowledge of this major historical event.
Keywords: Europe -- History -- 1848-1849.; Revolutions -- Europe -- History -- 19th century.; Europe -- Histoire -- 1848-1849.; Révolutions -- Europe -- Histoire -- 19e siècle.; HISTORY.; Revolutions; Europe; 1800-1899; History